E1 strength in light nuclei: Skyrme RPA analysis - Kvasil, J.; Repko, A.; Nesterenko, V. O.; Kleinig, W.; Reinhard, Paul-Gerhard (International Journal of Modern Physics E-Nuclear Physics, 2012)
The giant dipole resonance (GDR) in N = 28 isotones ( 48Ca, 50Ti, 52Cr, 54Fe) is analyzed in the framework of the Skyrme random-phase-approximation (RPA). Three Skyrme forces, SkM*, SLy6 and SV-bas, are used. The effects beyond RPA are simulated by the double folding procedure. We show that dipole strength exhibits a large collective shift, which testifies to a strong impact of the residual interaction and signals on considerable anharmonic effects. In 52Cr, a significant pairing impact is found. For exception of 50Ti, an acceptable agreement with the experiment data is obtained, which justifies the ability of Skyrme forces to describe GDR in light nuclei. © 2012 World Scientific Publishing Company.
CRIS-Team Scopus Importer:2023-07-24
Keywords: Dipole photoabsorption; light nuclei; N = 28 isotones; random-phase-approximation; Skyrme forces